The Gwich'in Traditional Caribou Skin Clothing Project: Repatriating Traditional Knowledge and Skills - Kritsch, Ingrid; Wright-Fraser, Karen (ARCTIC, 2002)
. The Gwich'in are the most northerly of the Athapaskan peoples occupying parts of the Yukon River drainage in Alaska and the Yukon Territory, and the northern Mackenzie Basin of the Northwest Territories. The project described here was sponsored by the Gwich'in who reside in the Northwest Territories. Traditionally their lands extended from the interior of the Yukon into the Mackenzie Basin and included the watersheds of the Peel, Mackenzie, and Arctic Red Rivers. Today, most NWT Gwich'in live in the four communities of Aklavik, Fort McPherson, Inuvik, and Tsiigehtchic (formerly called Arctic Red River). These communities all fall within the Gwich'in Settlement Area that was established by the Gwich'in Comprehensive Land Claim Agreement signed in 1992 with the Government of Canada. People in the Gwich'in Settlement Area are greatly interested in materials that were collected in earlier times and are now housed throughout the world in museums, archives, and private collections. These items represent a bygone era and have great historical, cultural, and sometimes spiritual meaning. Of particular interest is traditional Gwich'in summer clothing made of white caribou hides, sewn with sinew, and decorated with porcupine quills, trade beads, silverberry seeds, finges, and ochre. Distinctively styled and striking to look at, these garments are a testament to Gwich'in women's great skill and artistic expression. . It has been well over 100 years since Gwich'in traditional caribou skin clothing was made, and there are no examples of this clothing in either the Gwich'in communities or the Northwest Territories today. It has been over 50 years since porcupine quillwork was used as the primary decorative motif on Gwich'in jackets, slippers, and gloves. For the past two years, the Gwich'in Social and Cultural Institute (GSCI) has worked in partnership with the Prince of Wales Northern Heritage Centre (PWNHC) to create five replicas of a multipiece 19th-century Gwich'in traditional summer outfit that is housed at the ...